2021
DOI: 10.5469/neuroint.2020.00381
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Utilization of Preoperative Embolization for Spinal Metastases: A Study of the National Inpatient Sample 2005–2017

Abstract: Purpose: While previous studies have suggested that preoperative embolization of hypervascular spinal metastases may alleviate intraoperative blood loss and improve resectability, trends and driving factors for choosing this approach have not been extensively explored. Therefore, we evaluated the trends and assessed the factors associated with preoperative embolization utilization for spinal metastatic tumors using a national inpatient database.Materials and Methods: The National Inpatient Sample database of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Next, we discuss the clinical benefits of this procedure as reported in the primary literature, with benefits ranging from pain improvement as a palliative measure to significant decreases in blood loss intraoperatively. Overall, the use of preoperative embolization resulted in more favorable outcomes (6,(35)(36)(37).…”
Section: Clinical Outcomes After Tumor Embolizationmentioning
confidence: 99%
“…Next, we discuss the clinical benefits of this procedure as reported in the primary literature, with benefits ranging from pain improvement as a palliative measure to significant decreases in blood loss intraoperatively. Overall, the use of preoperative embolization resulted in more favorable outcomes (6,(35)(36)(37).…”
Section: Clinical Outcomes After Tumor Embolizationmentioning
confidence: 99%
“…Preoperative transcatheter arterial embolization (preoperative embolization) has emerged as an effective procedure for reducing intraoperative blood loss. [1][2][3][4][5][6] Furthermore, several metaanalyses have indicated that preoperative embolization of hypervascular metastatic tumors, such as renal cell carcinomas and thyroid cancers, can reduce intraoperative blood loss. [7][8][9] Additionally, there are several reports on the efficacy of cone-beam computed tomography arteriography (CTA) in preoperative embolization, which produced an excellent three-dimensional configuration of tumor-feeding blood vessels and required relatively few digital subtraction angiography (DSA) runs.…”
mentioning
confidence: 99%